Photocatalytic Hydrogen Production of Nd/Co Co-Doped BiFeO3 Nanoparticles With a Cellular Architecture - Gu, Yanhong; Zhou, Yan; Yang, Yanliang; Zhang, Xianghui; Zhang, Weiying; Zhao, Jianguo; Jia, Hong (Frontiers in Nanotechnology, 2021)
Bismuth ferrite (BFO) nanoparticles with general of the formula Bi1-xNdxFe1-yCoyO3 (x = 0, 0.05; y = 0, 0.05, 0.10, 0.15, 0.20) were prepared using a two-solvent sol-gel method. Interestingly, most of the samples exhibited a cellular architecture. Bandgap engineering of BFO nanoparticles was achieved by co-doping with Nd and Co. The bandgap of BFO could be tuned successfully from 1.58–2.06 eV. Under illumination with ultraviolet light, the concentration of methylene orange increased. The sample of Bi0.95Nd0.05Fe0.85Co0.15O3 produced a small amount of hydrogen (8.88 μmol g‑1 after 1.5 h), but the other samples did not produce detectable levels of hydrogen. In this research, the production of hydrogen occurred under illumination by ultraviolet light, demonstrating the splitting of pure water without the use of a sacriﬁcial reagent. A possible reason for this is that the conduction and valence band edges of BiFeO3 straddle the water redox potential. Consequently, it is possible to realize unassisted water splitting using BFO. The ferromagnetism of all samples increased linearly with the increase of dopant concentration, and the residual magnetization of the Bi0.95Nd0.05Fe0.80Co0.20O3 sample reached to 0.679 emu g‑1. Moreover, the magnetic properties of bismuth ferrite and Nd/Co Co-doped bismuth ferrite photocatalysts were also investigated to show the simple separation. These results demonstrate that BFO nanoparticles have potential applications in photocatalytic hydrogen production without the use of a sacriﬁcial reagent.